2010
DOI: 10.1590/s1679-87592010000700011
|View full text |Cite
|
Sign up to set email alerts
|

Hematological analysis of Micropogonias Furnieri, Desmarest, 1823, Scianidae, from two estuaries of Baixada Santista, São paulo Brazil

Abstract: Hematological alterations in fish are considered a useful tool to evaluate pathological processes resulting from the exposure to environmental pollutants. The whitemouth croaker Micropogonias furnieri is a common species in estuarine areas and potentially exposed to many contaminants. In the present study, the hematological characteristics of fish collected at two sites in Baixada Santista (Santos Estuarine System - SES, a polluted site; and the Estuary of Itanhaém River - EIR, unpolluted site) del was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Urban effluents consist of complex mixtures containing many toxic compounds, such as organic substances, pharmaceuticals and personal care products, metals, hydrocarbons, detergents, pesticides, drugs, and other toxic contaminants (Seriani et al 2010;Sibanda, Selvarajan, and Tekere 2015;Pereira et al 2016). However, urban effluents are frequently disposed into the aquatic ecosystems without prior treatment, a process that has biological effects and threatens aquatic organisms and human health alike (Alimba, Saliu, and Ubani-Rex 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Urban effluents consist of complex mixtures containing many toxic compounds, such as organic substances, pharmaceuticals and personal care products, metals, hydrocarbons, detergents, pesticides, drugs, and other toxic contaminants (Seriani et al 2010;Sibanda, Selvarajan, and Tekere 2015;Pereira et al 2016). However, urban effluents are frequently disposed into the aquatic ecosystems without prior treatment, a process that has biological effects and threatens aquatic organisms and human health alike (Alimba, Saliu, and Ubani-Rex 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1). São Vicente Estuary (SVE) is a part of the Santos Estuarine System, which is considered highly impacted by anthropic interventions and pollution (BOLDRINI;PEREIRA, 1987;MEDEIROS;BÍCEGO, 2004;SIQUEIRA et al, 2005;BÍCEGO et al, 2006;CESAR et al, 2006;HORTELLANI, et al, 2008;MARTINS et al, 2008;KIRSCHBAUM et al, 2009, SERIANI, et al, 2010. The SVE receives mainly domestic pollution from diffuse sources, specially sewage, stormwater and urban drainage, but contamination from domestic and industrial landfills is also considerable (LAMPARELLI et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The SVE receives mainly domestic pollution from diffuse sources, specially sewage, stormwater and urban drainage, but contamination from domestic and industrial landfills is also considerable (LAMPARELLI et al, 2001). Recent data on the SVE have shown that the discharge of contaminants from land-based sources has increased the concentration of several substances, many of which are already present in concentrations high enough to cause biological risks (LAMPARELLI et al, 2001;ABESSA et al, 2008;KIRSCHBAUM et al, 2009;SERIANI et al, 2010, PEREIRA, et al,2012. On the other hand, the Cananéia Estuary (CAN) presents lower levels of contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…The use of hematological parameters as indicators of fish health has been suggested by Hesser (1960). Hematological alterations in fish are considered a useful tool to evaluate pathological processes resulting from exposure to environmental pollutants (Seriani et al, 2010, 2011). Exposure to pollutants, pathogens, environmental stress, etc.…”
Section: Introductionmentioning
confidence: 99%